Gender Dimensions and the Inter-Relationship of Environmental Variables among Secondary School Students in Edo South Senatorial District, Nigeria - Odia, Agnes Anuoluwapo; Ogbemudiare, Benard (NIU Journal of Educational Research, 2025)
This study investigated gender dimensions and the inter-relationship of environmental variables among secondary school students in Edo South Senatorial District, Nigeria. The study was guided by four hypotheses, tested at the 0.05 level of significance. A descriptive correlational survey design was adopted. The population comprised 21,222 Senior Secondary School students, from which a sample of 1,202 students was selected using a simple random sampling technique. Two instruments were used: an achievement test and a questionnaire. Descriptive statistics, including frequency counts and percentages, were employed, while Pearson Product Moment Correlation and Wilks’ Lambda statistics were used to test the hypotheses. The hypotheses were rejected, indicating significant gender differences and relationship among students' environmental variables. The study concluded that gender influences secondary school students' environmental knowledge, attitude, and practices in Nigeria. The study therefore concludes that gender-inclusive teaching strategies such as hands-on projects, debates, real-world applications should be used in teaching students; and schools should encourage role models from all genders in environmental leadership. Keywords: Gender dimensions, Environmental variables, Students, Nigeria